Seasonal Variations in the Lipid Profile of the Ovarian Follicle in Italian Mediterranean Buffaloes - Michal Andrzej Kosior; Alfonso Calabria; Maria Paz Benitez Mora; Marco Russo; Giorgio Antonio Presicce; Natascia Cocchia; Salvatore Monti; Hilde Aardema; Bianca Gasparrini (Animals, 2022)
The reduced oocyte competence recorded during the non-breading season (NBS) is one of the key factors affecting the profitability of buffalo farming and limits the IVEP efficiency. The purpose of this experiment was to evaluate whether season influences the lipid content within the ovarian follicle in the Italian Mediterranean buffalo. Abattoir-derived ovaries were collected during the breeding season (BS) and the NBS, and different matrices (follicular fluid, oocytes, cumulus and follicular cells) were recovered. After the extraction of the apolar fraction, all samples were analyzed by H1 nuclear magnetic resonance and FF samples by gas chromatography–mass spectrometry. Seasonal differences in lipid composition were observed in all matrices. In particular, during the NBS, the triglyceride content was higher in the follicular fluid and in the oocytes but reduced in the follicular cells. Both cholesterol and phospholipids were reduced in the follicular fluid and follicular cells during the NBS. Furthermore, the total amount of non-esterified fatty acids was significantly increased in the follicular fluid. The seasonal variation in lipid profile of the follicle may, in part, account for the reduced buffalo oocyte competence during the NBS, due to the critical role played by lipids in regulating ovarian functions.